A study of the effectiveness of learning aids for the development of conceptual framework / Muhd Fitri Safwan Ghazali - Ghazali, Muhd Fitri Safwan; Wan Omar, Wan Noor Faaizah; Azizan, Hasnul Azwan; Shaharudin, Haszlin (Universiti Teknologi MARA, Kedah, 2020)
In this world, despite the individuals who are blessed with having a basic or good level of intelligence, some, on the other hand are experiencing difficulty in acquiring academic skills. Those skills are imperative for the success in writing, listening, speaking, calculating and reading. These difficulties may be the result of learning disability. There are children who struggle with learning on how to read, some in speaking and there are those with problems in arithmetic known as Dyscalculia. As stated by Kosc (1970), developmental dyscalculia affects mathematical ability in an individual. This condition is the result of a genetic or congenital disorder affecting the anatomicophysiological substrate of mathematical abilities maturation adequate to age, not the disorder of general mental functions. Individuals with dyscalculia will face challenges in performing calculation or arithmetic. Sadly, they currently face this disability with insufficient product or learning aids to overcome their condition. Product design is a process which a designer approaches problem solving with the guidance of analysis of a problem statement for the improvement on quality of life for the targeted end users. It is about visualizing, solving problem and providing a solution for the needs of users. According to Elsbach (2018), designers utilizes traditional tools to solve problems in the design thinking process. Design thinking is adopted as an approach for problem solving in the daily lives of consumers.